Deep brain stimulation of the subiculum in the treatment for refractory temporal lobe epilepsy due to unilateral mesial temporal lobe sclerosis - Sobstyl, Michał; Kowalska, Magdalena; Konopko, Magdalena; Wierzbicka, Aleksandra; Karamon, Karol; Nagańska, Ewa (Epilepsy & behavior reports, 2024)
•Hippocampal sclerosis is the most common cause of temporal lobe epilepsy.•Hippocampal sclerosis typically involves the hippocampus proper and dentate gyrus while sparing the subiculum.•Deep brain stimulation of the subiculum may be a treatment option for severe hippocampal sclerosis.•The subiculum may be a target for treating drug-resistant epilepsy.•Subicular stimulation reduced seizures by 67 % in our patient over 20 months. Temporal lobe epilepsy (TLE) is the most common form of drug-resistant epilepsy. The main pathological changes primarily involve hippocampal sclerosis (HS). Early resective surgery of the sclerotic hippocampus is typically associated with favorable clinical outcomes. However, not all patients are suitable candidates for resective surgery of mesial temporal lobe structures. Therefore, alternative treatment modalities should be considered. We present the case of a 50-year-old right-handed woman with left HS who underwent unilateral subiculum stimulation for drug-resistant epilepsy (DRE). Since the age of 10, the patient had been experiencing focal to bilateral tonic-clonic seizures (FBTCS). Despite multiple antiseizure medications, she experienced 12 to 17 FBTCS per month in the last two years. Due to concerns about potential memory decline and personal preferences, she refused resective surgery. As an alternative, the patient underwent left unilateral subiculum stimulation. The stimulation resulted in a nearly 67 % reduction in seizure frequency at the last follow-up (20 months after surgery). This case highlights that drug-resistant epilepsy may be effectively treated with subicular stimulation in patients with HS.